Investigation of cytokine levels in calves with sepsis - Guzelbektes, H; Sen, I; Aydogdu, U; Er, C; Coşkun, Alparslan (Journal of the Hellenic Veterinary Medical Society, 2022)
This study aimed to detect changes in clinical parameters, biochemical and serum cytokine levels in calves with sepsis. In the study, 34 calves diagnosed with sepsis according to clinical and laboratory results and 7 calves deemed to be healthy according to clinical and laboratory results were used. The blood sample was taken from vena jugularis for determination of hematological, biochemical, and cytokine levels. Significant changes were observed in the clinical parameters of calves with sepsis. Serum concentrations of IL-1β, IL-6, IL-10, TNF-α, and INF-γ were significantly increased (p < 0.05) in calves with sepsis compared to the control group. Also, a significant increase (p < 0.05) in serum BUN, creatinine, CK, and CK-MB levels and a significant decrease in TP level (p < 0.05) were determined in calves with sepsis compared to the control group. In conclusion, it was concluded that varying degrees of tissue/organ damage developed in calves with sepsis and cytokines played an important role in the development of inflammatory damage during sepsis.